PBX1 as Pioneer Factor: A Case Still Open - Grebbin, Britta M.; Schulte, Dorothea (Frontiers in Cell and Developmental Biology, 2017)
Pioneer factors are proteins that can recognize their target sites in barely accessible chromatin and initiate a cascade of events that allows for later transcriptional activation of the respective genes. Pioneer factors are therefore particularly well suited to initiate cell fate changes. To date, only a small number of pioneer factors have been identified and studied in depth, such as FOXD3/FOXA1, OCT4 or SOX2. Interestingly, several recent studies reported that the PBC transcription factor PBX1 can access transcriptionally inactive genomic loci. Here, we summarize the evidence linking PBX1 with transcriptional pioneer functions, suggest potential mechanisms involved and discuss open questions to be resolved.